The Case of Language Media Content (Memes) of the Pandemic. - Yashina, Maria; Karpina, Elena; Sinitsyna, Elena; Eranova, Natalia (Pertanika Journal of Social Sciences & Humanities, 2024)
The pandemic period gave rise to numerous memes in response to online audiences. In this article, the authors analyze the corpus of memes of Italian and Russian language media content during the 2020 pandemic from the perspective of a sociolinguistic approach, identifying the most significant groups of memes-markers as a response to the network audience involvement. The authors point out the ability to spread and maintain a stable form as an important component of these memes, as well as the emotional and phatic functions of a meme in the sociocultural space of the Internet community in Italy and Russia. Emerging in the media space and reproduced through reposting, memes have become a sociocultural phenomenon and can manage information flows. Besides, thanks to the halo of mass coverage, entertaining character, and affinity to the emotions of the addressee, the meme reflects the opinion of many users and does not need the category of authorship. It makes no difference whether a meme is a picture or has only a verbal component, and it is essential to be recognized in any of the many variations. At the same time, if the created meme has gained popularity and has become entrenched in the virtual environment, it can later form a way of realizing urgent needs or suppressing some trends while strengthening others.